Extreme downsizing in the surfactant-free synthesis of spin-crossover nanoparticles in a microfluidic flow-focusing junction. Issue 58 (1st June 2018) - González-Estefan, Juan H.; Gonidec, Mathieu; Daro, Nathalie; Marchivie, Mathieu; Chastanet, Guillaume
Abstract : A new surfactant-free, flow-focusing droplet microfluidic approach was developed as an important alternative to existing synthesis techniques for the preparation of spin crossover nanoparticles. Abstract : A new surfactant-free, flow-focusing droplet microfluidic approach was developed as an important alternative to existing synthesis techniques for the preparation of spin crossover nanoparticles. It enables great control of the mixing of the reactants, and produces crystals of [Fe(pyrazine)(Pt(CN)4 )] with an unexpected 20-fold downsizing compared to classical bulk synthesis.